The dynamics of cooperative bacterial virulence in the field. - Raymond, B; West, SA; Griffin, A; Bonsall, M (2012)
Laboratory experiments have shown that the fitness of microorganisms can depend on cooperation between cells. Although this insight has revolutionized our understanding of microbial life, results from artificial microcosms have not been validated in complex natural populations. We investigated the sociality of essential virulence factors (crystal toxins) in the pathogen Bacillus thuringiensis using diamondback moth larvae (Plutella xylostella) as hosts. We show that toxin production is cooperative, and in a manipulative field experiment, we observed persistent high relatedness and frequency- and density-dependent selection, which favor stable cooperation. Conditions favoring social virulence can therefore persist in the face of natural population processes, and social interactions (rapid cheat invasion) may account for the rarity of natural disease outbreaks caused by B. thuringiensis.